Optimization of Work Posture at PT. XYZ: Analysis of the Rapid Entire Body Assessment (REBA) Method to Improve Health and Productivity - Nismah Panjaitan; Niken Kristin Silitonga; Juni Arta Lubis; Muhammad Zaky Faris (Logistic and Operation Management Research (LOMR), 2024)
The study at PT. Fenyen Agro Lestari identified poor work postures that affect worker health and productivity. Using the REBA method, the boiler department had the highest risk (score 11), followed by the maintenance (score 6) and Laboratory (score 4). Immediate ergonomic improvements are recommended to reduce musculoskeletal disorders (MSDs).  The purpose of this research is to analyze the impact of poor working posture on workers' musculoskeletal health in various departments of PT. Fenyen Agro Lestari, Indonesia and recommend ergonomic improvements to reduce the risk of MSDs. The methodology involves REBA for postural assessment, collecting musculoskeletal complaints via questionnaires, and analyzing data to recommend ergonomic improvements. The findings revealed that poor postures cause significant musculoskeletal disorders, especially in the Boiler department, highlighting the need for ergonomic improvements. This study is novel in that it applies the Rapid Entire Body Assessment (REBA) method to a specific context within PT. Fenyen Agro Lestari, provides tailored ergonomic recommendations for multiple departments and addresses gaps in existing research on posture-related musculoskeletal disorders in the industry. The study’s limitations include a focus on only three departments, potential observer bias, and reliance on subjective questionnaire data, which may not fully capture all musculoskeletal issues or account for variations in individual worker experiences.